2014
DOI: 10.1152/japplphysiol.01270.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cachectic skeletal muscle response to a novel bout of low-frequency stimulation

Abstract: While exercise benefits have been well documented in patients with chronic diseases, the mechanistic understanding of cachectic muscle's response to contraction is essentially unknown. We previously demonstrated that treadmill exercise training attenuates the initiation of cancer cachexia and the development of metabolic syndrome symptoms (Puppa MJ, White JP, Velazquez KT, Baltgalvis KA, Sato S, Baynes JW, Carson JA. J Cachexia Sarcopenia Muscle 3: 117-137, 2012). However, cachectic muscle's metabolic signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 49 publications
7
79
0
Order By: Relevance
“…Exercise and repetitive muscle contractions also induce a transient activation of AMPK signaling (18). Interestingly, contracted cachectic muscle has an induction of AMPK signaling, which goes above an already elevated baseline level (50). Here, we report that the inhibition of myotube AMPK activity during LLC treatment can rescue suppressed mTORC1 signaling and protein synthesis.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Exercise and repetitive muscle contractions also induce a transient activation of AMPK signaling (18). Interestingly, contracted cachectic muscle has an induction of AMPK signaling, which goes above an already elevated baseline level (50). Here, we report that the inhibition of myotube AMPK activity during LLC treatment can rescue suppressed mTORC1 signaling and protein synthesis.…”
Section: Discussionmentioning
confidence: 62%
“…Muscle contraction-induced mTORC1 signaling is attenuated in severely cachectic Apc Min/ϩ mice, which exhibit chronic activation of muscle STAT3 (50). Interestingly, PDTC administration to these cachectic mice can rescue contraction-induced mTORC1 activation (50). We found that both anabolic and catabolic stimuli can activate muscle NF-B signaling, which may be related to differential functions of NF-B in muscle as it relates to inflammatory and mechanical signals (28).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A large body of work in rodents has demonstrated that muscle wasting with cancer cachexia is a double edge sword that involves protein synthesis suppression and activation of several protein degradation pathways [23-26]. The Apc Min/+ and C26 tumor-implanted mice have an established IL-6 dependent loss of skeletal muscle during cancer cachexia[9, 27, 28].…”
Section: Skeletal Muscle As a Target Of Il-6mentioning
confidence: 99%
“…In the cachectic Apc Min/+ mouse inhibition of IL-6 signaling through systemic administration of IL-6RAb attenuates further body weight and muscle loss without rescuing MPS. Additionally, the activation of mTOR signaling by both glucose and exercise is suppressed in the cachectic Apc Min/+ mouse [23, 26, 27]. However, this may be an indirect effect of IL-6, as IL-6 administration to C2C12 myotubes does not inhibit insulin stimulation of mTOR signaling [27].…”
Section: Skeletal Muscle As a Target Of Il-6mentioning
confidence: 99%